EVALUASI KINERJA DOSEN - Sidiq, Danang Majid; Samudra, Ahmad Hajar; Anwar, Khoirul (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
ABSTRACT Lecturer performance evaluation is a crucial aspect in improving the quality of higher education. This assessment covers not only teaching, but also research, community service, and academic participation. This article reviews commonly used evaluation methods such as student surveys, peer reviews, and analysis of student learning outcomes. Student surveys provide direct feedback on learning experiences, peer assessments offer professional perspectives, while learning outcomes serve as objective indicators of teaching effectiveness. This study employed a qualitative approach with descriptive methods, involving high-performing lecturers, students, and internal evaluators or peers as research subjects. Data were collected through in-depth interviews to gain a holistic understanding of how evaluations are implemented. The findings show that although the three evaluation methods have been applied, their implementation remains suboptimal. Student surveys tend to be influenced by subjective factors, peer assessments often lack standardized instruments, and student learning outcomes are underutilized. Furthermore, not all institutions follow up on evaluation results with clear professional development programs. The lack of transparency in the evaluation process has also led to resistance among some lecturers. Therefore, this study recommends the development of a more transparent, integrative, and technology-based evaluation system. Additionally, training for lecturers is essential to ensure that performance evaluations serve not only as assessment tools but also as a means for continuous professional growth and as a strategic component in enhancing the overall quality of higher education. ABSTRAK Evaluasi kinerja dosen merupakan aspek penting dalam meningkatkan mutu pendidikan tinggi. Penilaian ini mencakup tidak hanya aspek pengajaran, tetapi juga penelitian, pengabdian masyarakat, dan partisipasi akademik. Artikel ini mengulas metode evaluasi yang umum digunakan, seperti survei mahasiswa, penilaian sejawat, dan analisis hasil belajar mahasiswa. Survei mahasiswa memberikan umpan balik langsung atas pengalaman belajar, penilaian sejawat menyajikan perspektif profesional, sedangkan analisis hasil belajar menjadi indikator objektif efektivitas pengajaran. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, melibatkan dosen berkinerja baik, mahasiswa, serta tim evaluasi atau rekan sejawat sebagai subjek penelitian. Data diperoleh melalui wawancara mendalam untuk mendapatkan gambaran yang holistik dari pelaksanaan evaluasi. Hasil penelitian menunjukkan bahwa meskipun ketiga metode evaluasi telah diterapkan, pelaksanaannya belum sepenuhnya optimal. Survei mahasiswa cenderung dipengaruhi oleh faktor subjektif, penilaian sejawat belum didukung oleh instrumen baku, dan analisis hasil belajar belum dimanfaatkan secara maksimal. Selain itu, ditemukan bahwa tidak semua institusi menindaklanjuti hasil evaluasi dengan program pengembangan dosen yang jelas. Ketidakjelasan proses evaluasi juga menyebabkan resistensi dari sebagian dosen. Oleh karena itu, penelitian ini merekomendasikan pengembangan sistem evaluasi yang lebih transparan, integratif, dan berbasis teknologi informasi, serta perlunya pelatihan bagi dosen agar evaluasi dapat digunakan sebagai alat pengembangan profesional yang berkelanjutan dan strategis dalam peningkatan mutu pendidikan tinggi.